2002
DOI: 10.1902/jop.2002.73.2.167
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Conventional Periodontal Maintenance Versus Scaling and Root Planing With Subgingival Minocycline

Abstract: Scaling and root planing and subgingival minocycline in experimental sites took little time (<5 minutes/appointment), but resulted in more probing depth reduction and less frequent bone height loss than conventional periodontal maintenance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 31 publications
4
31
0
1
Order By: Relevance
“…The observed increase in bone density in group I is in agreement with the observation of Bezerra et al (5) who found that the animals subjected to 7 days of treatment for periodontitis with subcutaneous Mx (0.75, 1.5, 3 mg/ Kg) exhibited a dose-dependent inhibition of alveolar bone loss that was significantly different from that of untreated groups. The current study results of group II are in accordance with those of a previous study (44), where minocycline microspheres application diminished bone resorption and increased alveolar bone height.…”
Section: In Vitro Determination Of the Antibacterial Activity Of Mh Gsupporting
confidence: 92%
“…The observed increase in bone density in group I is in agreement with the observation of Bezerra et al (5) who found that the animals subjected to 7 days of treatment for periodontitis with subcutaneous Mx (0.75, 1.5, 3 mg/ Kg) exhibited a dose-dependent inhibition of alveolar bone loss that was significantly different from that of untreated groups. The current study results of group II are in accordance with those of a previous study (44), where minocycline microspheres application diminished bone resorption and increased alveolar bone height.…”
Section: In Vitro Determination Of the Antibacterial Activity Of Mh Gsupporting
confidence: 92%
“…This material has been used in combination with hydroxyapatite to prepare microspheres containing amoxicillin, amoxicillin-clavulanic acid or erythromycin [106]. In Table 1, we provide a few examples of polymeric materials that were been used for periodontal applications [82,91,93,99,101,102,107-110,116-118,123,125,126]. …”
Section: Microparticulate Delivery Systems and Periodontal Diseasesmentioning
confidence: 99%
“…Studies for determining the clinical efficacy of microspheres containing minocycline (Arestin) in comparison with that of a chlorhexidine gel as an adjunct to mechanical debridement of incipient peri-implant infections was carried out by Renvert et al [117,118]. The results demonstrated that local use of the microencapsulated antibiotic as an adjunct to mechanical treatment was effective for peri-implant lesions, with better results than with chlorhexidine gel.…”
Section: Microparticulate Delivery Systems and Periodontal Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…[89] Various locally delivered antimicrobials have been used aiming at inhibition of the pathogens or modulation of the inflammatory response, which include tetracycline, metronidazole, doxycycline, minocycline, and chlorhexidine. [101112131415]…”
Section: Introductionmentioning
confidence: 99%